A conscious rethink: Why is brain tissue commonly preserved in the archaeological record? Commentary on: Petrone P, Pucci P, Niola M, et al. Heat-induced brain vitrification from the Vesuvius eruption in C.E. 79. N Engl J Med 2020;382:383-4. DOI: 10.1056/NEJMc1909867. Issue 1 (1st January 2020) - Morton-Hayward, Alexandra L.; Thompson, Tim; Thomas-Oates, Jane E.; Buckley, Stephen; Petzold, Axel; Ramsøe, Abigail; O'Connor, Sonia; Collins, Matthew J.
ABSTRACT: Brain tissue is ubiquitous in the archaeological record. Multiple, independent studies report the finding of black, resinous or shiny brain tissue, and Petrone et al. [2020 "Heat-induced Brain Vitrification from the Vesuvius Eruption in C.E. 79." N Engl J Med . 382: 383–384; doi:10.1056/NEJMc1909867] raise the intriguing prospect of a role for vitrification in the preservation of ancient biomolecules. However, Petrone et al. (2020) have not made their raw data available, and no detailed laboratory or analytical methodology is offered. Issues of contamination and misinterpretation hampered a decade of research in biomolecular archaeology, such that addressing these sources of bias and facilitating validation of specious findings has become both routine and of paramount importance in the discipline. We argue that the evidence they present does not support their conclusion of heat-induced vitrification of human brain tissue, and that future studies should share palaeoproteomic data in an open access repository to facilitate comparative analysis of the recovery of ancient proteins and patterns of their degradation. GRAPHICAL ABSTRACT: